2017
DOI: 10.1093/nar/gkx921
|View full text |Cite
|
Sign up to set email alerts
|

StemMapper: a curated gene expression database for stem cell lineage analysis

Abstract: Transcriptomic data have become a fundamental resource for stem cell (SC) biologists as well as for a wider research audience studying SC-related processes such as aging, embryonic development and prevalent diseases including cancer, diabetes and neurodegenerative diseases. Access and analysis of the growing amount of freely available transcriptomics datasets for SCs, however, are not trivial tasks. Here, we present StemMapper, a manually curated gene expression database and comprehensive resource for SC resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…After reviewing almost all cancer single-cell sequencing studies, we concluded 14 crucial functional states of cancer cells, including stemness, invasion, metastasis, proliferation, EMT, angiogenesis, apoptosis, cell cycle, differentiation, DNA damage, DNA repair, hypoxia, inflammation and quiescence. To characterize these functional states for cancer single cells, we built the corresponding gene signatures through searching literatures and known databases (including some general databases, such as Gene Ontology (17) and MSigDB (18), and some specialized databases, such as Cyclebase (19), HCMDB (20) and StemMapper (21)) (Supplementary Table S2). For most of the signatures, the collected genes that were mentioned in more than two resources were kept.…”
Section: Methodsmentioning
confidence: 99%
“…After reviewing almost all cancer single-cell sequencing studies, we concluded 14 crucial functional states of cancer cells, including stemness, invasion, metastasis, proliferation, EMT, angiogenesis, apoptosis, cell cycle, differentiation, DNA damage, DNA repair, hypoxia, inflammation and quiescence. To characterize these functional states for cancer single cells, we built the corresponding gene signatures through searching literatures and known databases (including some general databases, such as Gene Ontology (17) and MSigDB (18), and some specialized databases, such as Cyclebase (19), HCMDB (20) and StemMapper (21)) (Supplementary Table S2). For most of the signatures, the collected genes that were mentioned in more than two resources were kept.…”
Section: Methodsmentioning
confidence: 99%
“…However, this set contains genes associated with pluripotency, such as Nanog , Klf2 , Klf4 , Klf5 , Zfp42/Rex1 , Sox2 , Esrrb , Nr0b1 , Dppa5a , and Zfp462 (Table S2), arguing for a delayed or restrained differentiation potential of Cited2 -depleted ESC. We also compared the set of genes upregulated in Cited2 -depleted cells with publicly available transcriptomics datasets related to stem cells using StemMapper 32 . This analysis confirmed that upregulated genes at D4 of differentiation in Cited2 -control cells distinguish between different cell lineages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Stem cell fate decisions, including the determination of cellular identity, are intimately linked to gene expression networks with each decision driven by wide-spread transcriptional changes ( Walker et al, 2007 ; Julian et al, 2013 , 2017b ; Julian and Blais, 2015 ; Pinto et al, 2018 ; Abdolhosseini et al, 2019 ; Wells and Choi, 2019 ). Transcriptional regulation does not function in isolation, however.…”
Section: Metabolic Organelle Network Regulate Stem Cell Fatementioning
confidence: 99%